Side Effects to Systemic Glucocorticoid Therapy in Dogs Under Primary Veterinary Care in the UK - Elkholly, Doaa A.; Brodbelt, Dave C.; Church, David B.; Pelligand, Ludo; Mwacalimba, Kennedy; Wright, Andrea K.; O'Neill, Dan G. (Frontiers in Veterinary Science, 2020)
Objectives: Systemic glucocorticoids are widely used in companion animals. This study aimed to estimate the frequency, describe the characteristics and to evaluate risk factors for common side effects to systemic glucocorticoid therapy in dogs under primary veterinary care in the UK. Methods: A cohort study using VetCompass™ data from 455,557 dogs under primary veterinary care during 2013 estimated the frequency of side effects to systemic glucocorticoid therapy occurring within 31 days of therapy. Risk factors for the most common side effects, polyuria and polydipsia (PUPD), were evaluated using multivariable logistic regression modeling (P < 0.05). Results: During 2013, 28,472 study dogs received systemic glucocorticoids (6.2%, 95% CI 6.2–6.3). Review of the records of 3,000 randomly selected treated dogs identified 148 (4.9%, 95% CI 4.2–5.7%) dogs with at least one side effect recorded within 31 days of therapy. The most frequent side effects were polydipsia (39.2% of total presenting signs), polyuria (28.4%), vomiting (16.2%) and diarrhea (14.9%), dogs receiving only oral systemic glucocorticoids (odds ratio, OR: 3.72) and dogs receiving both oral and injectable systemic glucocorticoid (OR: 10.71) had increased odds of PUPD compared with dogs receiving only injectable systemic glucocorticoid. Focusing on the active substance used, treatment with prednisolone tablets only (OR: 3.53) and treatment with both prednisolone tablets and injectable dexamethasone sodium phosphate (OR: 7.62) showed increased odds of PUPD compared to treatment with injectable dexamethasone sodium phosphate only. Brief: These results can assist veterinarians to optimize therapeutic selection for reduced side effect, to inform owners on common side effects, and help protect the welfare of pets and their owners.